The Contextualization of Ḥifẓ Al-'Irḍ on Hoax News (A Study on Imam Tājuddīn al-Subkī’s Maqāṣīd al-sharī’a) - Khairul Hamim; Lalu Supriadi (Ulumuna, 2020)
This study examines Tājuddīn al-Subkī’s concept of ḥifẓ al-‘irḍ, as an essential part of maqāṣīd al-sharī’a, and uses it to analyze hoax news. To limit this study, the authors focuse on two crucial aspects. First, what is the concept of ḥifẓ al-‘irḍ according to Imam Tājuddīn al-Subkī? Second, how to contextualize ḥifẓ al-‘irḍ in the contemporary time to approach hoax news? This library research uses content and critical analysis to Tājuddīn al-Subkī’s thoughts, which are contained the works written by himself and those written by scholars after him. This study argues that al-Subkī initiated the concept of ḥifẓ al-‘irḍ (maintaining honor). As an essential part of maqāṣīd al-sharī’a, ḥifẓ al-‘irḍ must be held in addition to five other main purposes, namely maintaining the soul, religion, reason, lineage, and treasure. According to al-Subkī, defending honor can be equated with keeping the lineage because the two have a close and robust relationship, especially when discussing adultery and qadhf/قذف (accusing people of committing adultery). The spread of hoaxes today is like qadhf in Islamic law. The hoax spread must be stopped because it causes damage to the life of society, nation, and state. Preventing injury and realizing benefits are at the core of maqāṣīd al-sharī’a.